Reconstructive Habits: John Dewey on Human Functioning - Jaitner, David (ETHICS IN PROGRESS, 2018)
The academic strife to parse, investigate and adjust human functioning establishes varieties of at least three key concepts: behavior, action, activity. Depending on the general approach chosen, human functioning is therefore defined in a certain way and in a certain understanding of freedom. Within this paper, the pragmatist considerations of John Dewey (1859-1952) offer a sophisticatedly formulated theory of human functioning that, undoubtedly, takes action-theoretical paths but formulates underlying assumptions in a significantly unusual way. The main focus is to outline the theory in such a way that clearly shows the unusual as part of the usual and the usual as part of the unusual. For this purpose, the first section defines action as the basic category of Deweyan human functioning where sensory stimuli, registering elements and motor responses play a leading role, but according to Dewey questions the today still popular model of behaviorist psychology, that positions isolated and a-cultural stimulus-response-procedures in the human organism. The second section affirms the theoretical inclusion of deliberative elements that constitute human action, but according to Dewey witnesses their substantial and rather sporadic significance in a predominantly habitual human functioning. The conclusive section outlines the possibilities and limits of transforming habitually inured patterns of human conduct by means of reconstructive habits.